GaN-based blue laser diode with 6.0 W of output power under continuous-wave operation at room temperature. (November 2021) - Liang, Feng; Zhao, Degang; Liu, Zongshun; Chen, Ping; Yang, Jing; Duan, Lihong; Shi, Yongsheng; Wang, Hai
Abstract: In this work, we reported the room-temperature continuous-wave operation of 6.0 W GaN-based blue laser diode (LD), and its stimulated emission wavelength is around 442 nm. The GaN-based high power blue LD is grown on a c -plane GaN substrate by metal organic chemical vapor deposition (MOCVD), and the width and length of the ridge waveguide structure are 30 and 1200 μ m, respectively. The threshold current is about 400 mA, and corresponding threshold current density is 1.1 kA/cm 2 .